Galactic Propagation of Cosmic Rays from Individual Supernova Remnants. (July 2015) - Nierstenhöfer, Nils; Graeser, Philipp; Schuppan, Florian; Tjus, Julia
Abstract: It is widely believed that supernova remnants are the best candidate sources for the observed cosmic ray flux up to the knee, i.e. up to ∼PeV energies. Indeed, the gamma-ray spectra of some supernova remnants can be well explained by assuming the decay of neutral pions which are created in hadronic interactions. Therefore, fitting the corresponding gamma spectra allows us to derive the spectra of cosmic rays at the source which are locally injected into our Galaxy. Using these spectra as a starting point, we propagate the cosmic rays through the Galaxy using the publicly available GALPROP code. Here, we will present first results on the contribution of those SNRs to the total cosmic ray flux and discuss implications.